Promotional Role of Pd Over Ni Catalyst Dispersed Over Sc‐ZrO₂ for Methane Partial Oxidation: Crystallinity and Reducibility Effects - Alwadai, Norah; Acharya, Kenit; Ibrahim, Ahmed A.; Alreshaidan, Salwa Bader; Bayazed, Mohammed O.; Osman, Ahmed I.; Alotaibi, Nawaf N.; Qahtan, Talal F.; Cao, Gui‐Ping; Kumar, Rawesh; Al‐Fatesh, Ahmed S. (Energy science & engineering, 2025)
ABSTRACT Natural emissions of the highly potent greenhouse gas methane cannot be completely prevented, but in the presence of O2, methane can be catalytically converted to hydrogen‐rich syngas. This reaction is specified as partial oxidation of methane (POM). Herein, Ni dispersed over “scandia‐stabilized‐zirconia” (5Ni/DSZ) and the promotional effect of Pd (0.01 to 0.1 wt%) are investigated for POM and characterized with surface area and porosity measurements, X‐ray diffraction, Raman spectroscopy, temperature‐programmed studies, and thermogravimetry. During the POM, the initial population of active Ni sites decreases in non‐promoted catalysts due to oxidation under oxygen, upon loading of 0.02 wt.% Pd over 5Ni/DSZ, the active site population is preserved against oxygen during the POM due to improved metal support interaction between Ni and long‐range order crystallites of support (like cubic ZrO2 and orthorhombic Sc2Zr5O13). 5Ni0.02 Pd/DSZ catalyst acquired more than 80% catalytic activity (CH4 conversion and H2 yield) with 2.5 H2/CO ratio at 600°C during 240 min on stream. The 5Ni0.02 Pd/DSZ catalyst also maintained more than 70% H2 yield with H2/CO ratio ~2 during 30 h time on stream. The thermostable 5Ni0.02 Pd/DSZ catalyst may be recommended for hydrogen‐rich syngas production with high H2‐yield through POM.